MISCONCEPTIONS IN THE CHEMISTRY TEACHING IN THE REPUBLIC OF MACEDONIA REGARDING THE OXIDATION REACTIONS OF MONOSACCHARIDES - Stojanovska, Marina; Šoptrajanov, Bojan; M. Petruševski, Vladimir (Macedonian Academy of Sciences and Arts, 2017)
The easy oxidation of the substances containing aldehyde groups using a mild oxidizing agents, such as solutions containing copper(II) or silver(I) ions, can provide a mean to detect the presence of carbohydrates known as reducing sugars. However, using such tests, it is not possible to distinguish between aldoses and ketoses because the alkaline conditions in the reaction system lead to tautomerization of the α-hidroxyketone and immediate oxidation of the product so that both glucose and fructose will react with the oxidizing agents (the Tollens’ and Fehling’s reagents). In fact, the reaction of fructose is even faster than that of glucose. A misinterpretation or simple neglect of these experimental facts is present in some textbooks in the Republic of Macedonia and this influences the chemistry teaching by creating misconceptions among students and teachers.